Analysis of Color Changes in Dental Enamel Following Exposure to Herbal Bleaching Agents: A Spectrophotometric In-vitro Study - Jyothi Lekshmi B.; Nair, Saranya S. (New Visions in Medicine and Medical Science Vol. 8, 2024)
Aim: This study aimed to evaluate the color change in enamel bleached with herbal bleaching agents using a spectrophotometer. Introduction: Tooth discoloration is a common concern affecting individuals' aesthetics, leading to an increased demand for tooth whitening procedures. Herbal bleaching agents have gained attention due to their perceived safety and efficacy. This study aimed to assess the effectiveness of Musa sapientum, Citrus sinensis, and Citrus limon in tooth whitening compared to hydrogen peroxide. Materials and Methods: Forty artificially stained premolars were randomly selected, and baseline color values were obtained using a spectrophotometer. The specimens were divided into four groups: Group 1 (n=10) treated with Musa sapientum, Group 2 with Citrus sinensis, Group 3 with Citrus limon, and Group 4 served as the control and treated with 35% hydrogen peroxide. Color difference (\(Δ\)E) was examined using a spectrophotometer. Results: All tested agents induced a significant color change (\(Δ\)E > 3.3). Musa sapientum demonstrated the most significant whitening effect compared to the citrus groups. Discussion: The findings suggest that herbal bleaching agents, particularly Musa sapientum, can effectively whiten teeth. However, further studies are needed to explore their long-term effects and safety profile. Conclusion: Within the limitations of this study, Musa sapientum exhibited superior tooth whitening efficacy compared to Citrus sinensis and Citrus limon but was inferior to hydrogen peroxide.